Gesundheitserziehung - die Ver(sozial)wissenschaftlichung der Gesundheitsaufklärung in den 1950er und 1960er Jahren = Health education and its (social) scientization in the 1950s and 1960s - Sammer, Christian (NTM, 2021)
The contemporary history of prevention is booming. By means of its preventative societal handling of health and illness, it illuminates exemplarily the transformation in concepts, institutions, and practice of the biopolitical governing of populations. In this regard health education is a decisive technology. However, up until now the history of health education, especially with regard to its methodological transformation during this period, as well as the relations between international developments and national adaption, has not been well studied. This gap will be filled to a certain extent by means of quantitative and qualitative analysis of three different anglophone journals. During the 1950s an international professional discourse was established, which constituted a scientific occupational area. This clearly required moving away from the traditional German model of a demonstrative mediation of medical knowledge, mainly through exhibitions, and to focus on the integration of knowledge and methodology from the social sciences. From the perspective of the BehaviouralSciences human action and the possibility of it being influenced were integrated within a network of mutual influencing factors: apparently only survey research on health attitudes and motivation as well as on its own efficacy could enable the health educators to successfully understand and change human behaviour-the prioritized purpose of health education. Through such a determination of purpose, means, and relevant knowledge, which was differently received and institutionalized in the FRG as well as in the GDR, the actors of the discourse assured themselves to be part of an international profession of health educators. However, more research and the implementation of their results did not fulfill their hopes of finding "recipes for steering human" behaviour.
Gesehen am 10.05.2021